Clinicopathological Evaluation of Odontogenic Jaw Cysts (Update Dental College Journal, 2016)
Background: Odontogenic cysts are the most common form of cystic lesions affecting the maxillofacial region and one of the main causes of the damage of these bones.Objective: To determine the frequency of different types of odontogenic jaw cysts diagnose among the Bangladeshi population.Study design: A descriptive observational study was made of 62 patients.Study setting and period: The study was done in the Department of Oral & Maxillofacial Surgery, Bangabandhu Sheikh Mujib Medical University, Shahbag, Dhaka-1000 from 1st March 2010 to 28th February2011.Participants: Sixty-two patients with cystic lesions in the maxillofacial region were selected for the study.Methods: Patients who attended in the Oral & Maxillofacial Surgery Department of BSMMU during the study period with suspective cystic lesion in the maxillofacial region were included in the study. After clinical diagnosis with odontogenic cysts all the patients were treated surgically either under local anesthesia or under general anesthesia if required. Cystic lining was then sent for histopathological confirmation. Data were collected from a total of 76 patients with a clinical diagnosis of odontogenic jaw cysts. Of those, data of 14 patients were not included in the analysis (Histopathology showed no cystic lesion in 6 patients and non odontogenic cyst in 8 patients). Therefore data of a total of 62 patients were analyzed for the purpose of the study. The study protocol was explained to the patients in detail before obtaining the informed consent from the patients. Patients were allocated for the study.Outcome Variable: The following variable were recorded: gender, age, site of the lesion, swelling, tooth mobility, carious tooth, discolored tooth, missing tooth, radiological features, impacted tooth and correlation with histological types.Results: Out of 76 histopathology reports analyzed, odontogenic cyst found in 62 cases (82%). The mean patient age was 28.06 years. The cysts were slightly more prevalent in females (52%). Radicular cyst was the most prevalent histological type (56%), followed by dentigerous cyst (21%), odontogenic keratocysts (15%) and residual cysts (8%). The most common location of the odontogenic cysts were in the maxilla (n=35) than mandible (n=27).Conclusion: The most frequently occurring lesion was radicular cyst and the site was the anterior region of the maxilla. The dentigerous cyst and odontogenic keratocyst were the next most common lesions and preferred site was in the ramus and angular region of the mandible.Update Dent. Coll. j: 2015; 5 (2): 30-39